2021
DOI: 10.1093/ofid/ofab300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Emerging B.1.1.7+E484K SARS-CoV-2 Isolates

Abstract: We report the genome of a B.1.1.7+E484K SARS-CoV-2 from southeastern Pennsylvania and compare to all high-coverage B.1.1.7+E484K genomes (n=235) available. Analyses showed the existence of at least 4 distinct clades of this variant circulating in the US, and the possibility of at least 59 independent acquisitions of the E484K mutation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Further, for all these variants there is evidence of a significant reduction in neutralization by the LY-CoV555/LY-CoV016 and other mAb treatments 56 , 70 74 . Collier and coworkers very recently reported that the introduction of the E484K mutation in the B.1.1.7 background (to account for the new VOC B.1.1.7 + E484K found in the virus isolated both in UK and in Pennsylvania, USA) 75 led to robust loss of neutralizing activity by 19 out of 31 vaccine-elicited antibodies and mAbs if compared with the decrease in sensitivity conferred by the mutations in B.1.1.7 alone 76 . Moreover, the E484Q/V/A/G/D mutations have been just described by Chen et al as critical in promoting escape not only from Eli Lilly mAbs but also from other similar therapeutics that are currently in clinical trials 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, for all these variants there is evidence of a significant reduction in neutralization by the LY-CoV555/LY-CoV016 and other mAb treatments 56 , 70 74 . Collier and coworkers very recently reported that the introduction of the E484K mutation in the B.1.1.7 background (to account for the new VOC B.1.1.7 + E484K found in the virus isolated both in UK and in Pennsylvania, USA) 75 led to robust loss of neutralizing activity by 19 out of 31 vaccine-elicited antibodies and mAbs if compared with the decrease in sensitivity conferred by the mutations in B.1.1.7 alone 76 . Moreover, the E484Q/V/A/G/D mutations have been just described by Chen et al as critical in promoting escape not only from Eli Lilly mAbs but also from other similar therapeutics that are currently in clinical trials 77 .…”
Section: Discussionmentioning
confidence: 99%
“…An additional substitution E484K was added to the original Alpha variant (Alpha+E484K) as this mutation occurred in many clinical isolates. 16 The spike genes from all recombinant viruses were sequenced to ensure no aberrant mutations. Comparable ratios of viral RNA copies versus plaque-forming units (RNA/PFU) were found for both WT and chimeric viruses when produced and analyzed on Vero E6 cells ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the Delta variant is represented by 47 distinct CCs. This adds granularity for investigating outbreaks, local patterns, and emerging variants within a particular lineage ( Moustafa et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%